Prevalence, underlying causes, and determinants of maternal near miss in Ethiopia: a systematic review and meta-analysis - Tesfay, Neamin; Hailu, Girmay; Begna, Dumesa; Habtetsion, Medhanye; Taye, Fitsum; Woldeyohannes, Fitsum; Jina, Ruxana (Frontiers in Medicine, 2024)
Background: Maternal near miss (MNM) is one of the newly adopted assessment parameters to gauge the quality of maternity care. In Ethiopia, several studies have been conducted to investigate the incidence, underlying causes, and determinants of MNM. However, the findings from those studies vary greatly and are largely inconsistent. Thus, this review aims to more robustly estimate the pooled prevalence, identify underlying causes, and single out determinants of MNM in Ethiopia.Methods: Studies were searched from international databases (PubMed/Medline, Cochrane Library, and Embase databases) and other potential sites. All observational studies were included.Heterogeneity between studies was checked using Cochrane Q test statistics and I 2 test statistics and small study effects were checked using Egger's statistical test at a 5% significance level.Outcome measures were overall and specific underlying causes (obstetrics hemorrhage, hypertensive disorder pregnancy, pregnancy-related infection) rates of MNMs per 10000 live births.The meta-analysis included 43 studies consisting of 77240 MNM cases. The pooled prevalence MNM per 1000 live births in Ethiopia was 54.33 (95% CI: 33.93 to 85.89). Between-2 | P a g e study heterogeneity was high (I 2 = 100%, p < 0.0001), with the highest rate observed in Amhara region (384.54 per 1000). The prevalence of obstetrics hemorrhage (14.56 per 1000) was higher than that of hypertensive disorder pregnancy (12.67 per 1000) and pregnancy-related infections (3.55 per 1000) were identified as underlying causes. Various factors, including socio demographic characteristics, previous medical and obstetrics history as well as access to and quality of care obtained, were associated with MNM.Almost six women encounter near miss among a hundred live births in Ethiopia.Obstetric hemorrhage and hypertensive disorder pregnancy were the most common underlying causes of MNM. Both individual and facility level determinants were found to be associated with MNM. Considering the magnitude and identified factors, tailored measures should be taken at every stage of the continuum of care.Systematic review registration number. CRD42023395259